Quantitation of the Effect of ErbB2 on Epidermal Growth Factor Receptor Binding and Dimerization - Li, Yu; Macdonald-Obermann, Jennifer; Westfall, Corey; Piwnica-Worms, David; Pike, Linda J. (The Journal of biological chemistry, 2012)
The epidermal growth factor (EGF) receptor is a member of the ErbB family of receptors that also includes ErbB2, ErbB3, and ErbB4. These receptors form homo- and heterodimers in response to ligand with ErbB2 being the preferred dimerization partner. Here we use 125I-EGF binding to quantitate the interaction of the EGF receptor with ErbB2. We show that the EGFR/ErbB2 heterodimer binds EGF with a 7-fold higher affinity than the EGFR homodimer. Because it cannot bind a second ligand, the EGFR/ErbB2 heterodimer is not subject to ligand-induced dissociation caused by the negatively cooperative binding of EGF to the second site on the EGFR homodimer. This increases the stability of the heterodimer relative to the homodimer and is associated with enhanced and prolonged EGF receptor autophosphorylation. These effects are independent of the kinase activity of ErbB2 but require back-to-back dimerization of the EGF receptor with ErbB2. Back-to-back dimerization is also required for phosphorylation of ErbB2. These findings provide a molecular explanation for the apparent preference of the EGF receptor for dimerizing with ErbB2 and suggest that the phosphorylation of ErbB2 occurs largely in the context of the EGFR/ErbB2 heterodimer, rather than through lateral phosphorylation of isolated ErbB2 subunits. Background: ErbB2 is the preferred dimerization partner for the epidermal growth factor (EGF) receptor. Results: Heterodimerization with ErbB2 increases the affinity of the EGFR for EGF and increases the level of dimers maintained at any given concentration of EGF. Conclusion: ErbB2 modulates EGF receptor affinity and dimer stability. Significance: This study elucidates the molecular basis for the enhanced binding of EGF to EGFR/ErbB2 heterodimers.